Synthesis and characterization of chitosan-based pH-sensitive biofilm: An experimental design approach for release of vitamin B12 - Onal, Ali; Demir, Hulya; Kaplan Ince, Olcay; Ince, Muharrem (Italian Journal of Food Science, 2024)
Hydrogels because of their unique potentials, such as highwater content and hydrophilicity, are of interest for the controlled release of drug molecules. In the present study, a biofilm was produced using chitosan, a natural polymer. Characterization analyses of the synthesized biofilm were performed using Fourier-transform infrared spectroscopy (FT-IR), thermogravimetric analysis-differential thermal analysis, x-ray diffraction, and scanning electron microscopy-energy dispersive x-ray spectrometry. The analysis results of the film before loading were compared to the analysis made after adding vitamin B12 to the film. The release percentage of vitamin B12 was investigated by using ultraviolet-visible spectrophotometery. The FT-IR bands of vitamin B12 were in the range of 2,800-3,500 cm-1 and 1,000 cm-1-1,750 cm-1. When pH increased from 3 to 7, release of vitamin B12 from the biopolymer increased up to pH 5. While examining the release potential, parameters, such as pH, initial concentration of vitamin B12, release time, and solution volume, were optimized by using response surface methodology. It was determined that with the increase in release time and the initial concentration, pH contributed positively to the release of vitamin B12. The following conditions were determined for release of vitamin B12 from the biofilm: pH: 4.2, initial concentration of vitamin B12: 54.0 mg L-1, the release time: 117 min, and volume of solution: 2.1 mL. The analysis of variance results showed that the determination coefficients for the use of synthesized biofilm in vitamin B12 release were high and R2 =0.9704.